Epidemiological and economical approach in animal health management - Calvin W. Scwabe (Hemera Zoa, 1988)
A variety of patterns for delivery of rural veterinary services during the past 200 years demonst rate that, for no country have purely or largely curative services been economically viable without direct or indirect govermental subsidization. Te impact of such efforts upon overall productivity were rarely, if ever convincingly demonstrated ; yet veterinary curricula still continue to emphasize practice skills solely applicable to individual animal curative medicine. At the same time, govermental disease control programmes on a population level were almost exclusively mass campaigns conducted without benefit of sufficient baseline information on relevant distributions of diseases of causally related variables, therefore not optimally focused for best uses of scarce resources, not seldom able to accurately reflect their economic advantages in terms of benefits and costs.